ANALISIS PROMOSI PENGGUNAAN MEDIA SOSIAL (INSTAGRAM, FACEBOOK, WHATSAPP) TERHADAP RESPON KONSUMEN PADA TOKO PUSAT OLEH – OLEH “RUMAH MADUMONGSO” KEDIRI - Puspa, Nova Vidya; Icshannudin; Suhardi, Suhardi (Universitas Nusantara PGRI Kediri, 2022)
The objectives of this study are as follows: 1) To analyze promotions using Instagram social media to consumer responses at the central store by – by